Perancangan Interior Cafe dan Bistro “Salt & Sugar”di Surabaya - Stephanie Sophie; Yusita Kusumarini; Meirina Kuncahyowati (Intra, 2019)
Salt & Sugar is one of the culinary business that is located in Surabaya. There is no permanent design for the interior and that cause lack of identity in the eye of the customer. This problem are caused by limited space, on the other hand because of the room capacity are limited, often overcrowded. With establishing brand image Salt & Sugar in the interior, can create the suitable interior design. also arranging the room to reach maximum capacity. In this design, it use design thinking methods that have three main stages, inspiration (understand, observe, pov), ideation (ideate, propotype, test), implementation (story telling, pilot, business model).The result of this design is three design modules that can show the brand image of Salt & Sugar and arrange the room to reach maximum capacity with using space-saving furniture, it consists of multifunctional furniture and folding furniture.